The comparative performance of land sharing, land sparing type interventions on place-based human well-being - Carmenta, Rachel; Steward, Angela; Albuquerque, Adrielly; Carneiro, Renan; Vira, Bhaskar; Estrada-Carmona, Natalia (2022)
This dataset describes the five most important constituents of human wellbeing listed by 270 head households – HH in the Brazilian Amazon. Households predominantly work in agriculture and are located across contrasting interventions, including sectoral (i.e., Protected Area – 70 HH, Soy conventional production – 60 HH) and integrated (i.e., Extractive reserve – 70 HH and National Forest – 70HH) efforts. Each of the most important constituents of human wellbeing was reclassified into the three universal dimensions - material, quality of life, and relational - and sub-domains. Responses were collected in Pará in 2019. (2022-06-22)